Supervision Mechanism of Fulfillment of Provincial Minimum Wage - Laode Muhammad Isman Hardiansyah; Marwati Riza; Anshori Ilyas (IHSA Institute, 2022)
Problem of not optimal supervision by the Transmigration and Manpower Office of Southeast Sulawesi on companies in Southeast Sulawesi in the implementation of the Provincial Minimum Wage (UMP). This can be seen from the existence of companies in Southeast Sulawesi that have not paid wages in accordance with the predetermined Provincial Minimum Wage (UMP), even though the agency has mandated each company, so that all pay wages in accordance with the Provincial Minimum Wage (UMP). This study aims to determine: 1) How is the Mechanism of Supervision Authority on the Fulfillment of the Provincial Minimum Wage.This research is a normative and empirical research located in Southeast Sulawesi. Data obtained through surveys, interviews, and documentation. Overall data were analyzed quantitatively. Based on the results of the research that: 1) That the supervision of the implementation of the Provincial Minimum Wage by the Office of Transmigration and Manpower at companies in Southeast Sulawesi in general has been carried out well. However, 1 out of 10 indicators has not been implemented or is not good, namely requests for reports and information verbally from employees